Properties of the corticostriatal long term depression induced by medial prefrontal cortex high frequency stimulation in vivo - Braz, Bárbara Yael (2017)
Repetitive stimulation of cognitive forebrain circuits at frequencies capable of inducing corticostriatal long term plasticity is increasingly being used with therapeutic purposes in patients with neuropsychiatric disorders. However, corticostriatal plasticity is rarely studied in the intact brain. Our aim was to study the mechanisms of corticostriatal long term depression (LTD) induced by high frequency stimulation (HFS) of the medial prefrontal cortex in vivo. Our main finding is that the LTD induced in the dorsomedial striatum by medial prefrontal cortex HFS in vivo (prefrontostriatal LTD) is not affected by manipulations that block or reduce the LTD induced in the dorsolateral striatum by motor cortex HFS in brain slices, including pharmacological dopamine receptor and CB1 receptor blockade, chronic nigrostriatal dopamine depletion, CB1 receptor genetic deletion and selective striatal cholinergic interneuron (SCIN) ablation. Conversely, like in the hippocampus and other brain areas, prefrontostriatal LTD is NMDA receptor dependent. Thus, we describe a novel form of corticostriatal LTD that operates in brain circuits involved in reward and cognition and could be relevant for understanding the therapeutic effects of deep brain stimulation.